ANALISIS KINERJA KEUANGAN KOPERASI: STUDI KASUS PADA KUD MANUNGGAL ABADI DI DESA TAPUNG LESTARI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Tumarjiyanto, Tumarjiyanto; Salman, Salman (DINAMIKA PERTANIAN, 2017)
The objective of this research was to analysis the finantial performance of Village Unit Cooperation according to rentability ratio, solvability ratio, liquidity ratio and activity ratio. This research was conducted on KUD Manuggal Abadi in Lestari Tapung Village from June to October 2014. The results showed that the operating income ratio of KUD Manunggal Lestari was able to reduce operatig costs. The rate of return on investment; the ability of KUD to manage capital for get profit was relative bad. The rate of return for the owners showed that the capital owned cooperation was not sufficient rentable in get net wealth. The solvability atio showed that the debt total to equity ratio; the finantial performance of KUD was less solvable in paying indebtedness and the debt total to total of asset capital of KUD in long term was not able to ensure safety for creditor. The liquidity ratio showed that KUD is availabe on liquit condition dan the effectivity ratio KUD Manuggal Abadi is good condition. The ratio of cost of goods sold on sales and operational charge on sales were good.